Deconjugated urinary metanephrine, normetanephrine and 3-methoxytyramine in laboratory diagnosis of pheochromocytoma and paraganglioma - Bílek, R; Zelinka, T; Vlček, P; Dušková, J; Michalský, D; Novák, K; Bešťák, J; Widimský, J (Physiological research, 2015)
This work discusses the clinical performance of deconjugated metanephrine (MN), normetanephrine (NMN) and 3-methoxytyramine (3MT) determined in the basal first morning urine using a chromatographic method with electrochemical detection for the clinical diagnosis of pheochromocytoma (PHEO) and paraganglioma (PGL). Urine samples were collected from 44 patients (36 with PHEO, 8 with PGL) aged 54+/-17 (20-78) years (22 females, 22 males). A sampling of biological materials was performed preoperatively and about one week, six months and one year after adrenal gland surgery. The control group consisted of 34 PHEO/PGL patients more than 4 months after adrenal gland surgery. All subjects in the control group were without a diagnosis of PHEO or PGL. Clinical sensitivity was 55 % for MN, 64 % for NMN, 80 % for combination of both MN and NMN, and only 23 % for 3TM. Clinical specificity calculated from the control group was 93 % for MN, 95 % for NMN, 95 % for the combination MN and NMN, and 97 % for 3TM. Cut-off values for deconjugated metanephrines in the basal urine were 310 (MN), 690 (NMN) and 250 microg/l (3MT). Chromatographic determination of deconjugated urinary metanephrines, which is simple without the necessity of special laboratory material, can serve for the screening of PHEO or PGL patients. Urine NMN and 3MT exerts an association to malignity, and all markers are associated with tumor mass. However, the principal laboratory diagnosis of PHEO or PGL must be based on plasma-free metanephrines and plasma chromogranin A with better performance in the laboratory diagnosis of PHEO or PGL.
Keywords: biologické markery; Aged; vysokoúčinná kapalinová chromatografie; Pheochromocytoma; lidé středního věku; senioři; Clinical Laboratory Techniques; lidé; Adult; Middle Aged; nádory nadledvin; dospělí; dopamin; Normetanephrine; Adrenal Gland Neoplasms; metanefrin; Female; paragangliom; Biomarkers; feochromocytom; Male; Metanephrine; ženské pohlaví; mladý dospělý; Humans; mužské pohlaví; Young Adult; normetanefrin; Dopamine; Chromatography, High Pressure Liquid; klinické laboratorní techniky; Paraganglioma